Comparative study on the microbiota of colostrum and nipple skin from lactating mothers separated from their newborn at birth in China - Du, Yanli; Qiu, Qing; Cheng, Jing; Huang, Zhili; Xie, Ruixia; Wang, Lu; Wang, Xiangyu; Han, Zongli; Jin, Gang (Frontiers in Microbiology, 2022)
Increasing studies have found breast milk (BM) contains its own microbiota. However, the route through which microbes enter the BM is still unclear. In order to verify the entero-mammary pathway of BM, we designed a rigorous study that prevented oral bacteria from contaminating the breast and nipple skin (NS) during baby nursing. Thirty-one healthy, postpartum mothers living in southern China who were immediately separated from their newborn after delivery were enrolled in this study. Using an aseptic protocol for sampling, sterile water was used to wash the NS and was then collected. Then the first drop of BM was discarded and colostrum was collected manually. Amplicon sequencing was performed targeting the V3–V4 region of the bacterial 16S rRNA gene, and the differences between the microbiota of the colostrum and NS were analyzed. Additionally, the effects of environmental factors such as the delivery mode and intrapartum antibiotic exposure on the diversity of the colostrum microbiota were also analyzed. We found significant differences in the α diversity and richness between the BM and NS as evidenced by richness, Chao1, and Simpson indices. There were 170 operational taxonomic units (OTUs) shared by colostrum and NS, while 111 and 87 OTUs were unique respectively, as well as a clear distinction in OTUs by unifrac binary analysis between them. Linear Discriminant Analysis effect size analysis found that anaerobes such as Bifidobacterium and Pantoea, at the genus level and enterobacteria including Enterobacteriaceae at the family level, were predominant in the colostrum, while the main bacteria on the NS were Bacteroides, Staphylococcusand and Parabacteroides at the genus level et al. BM is colonized by bacteria prior to baby suckling, and the diversity of the colostrum microbiota differs from that of the NS. The predominant microbiota taxa in BM indicated that they were likely to be transferred to the breast through the intestinal tract. Our study provides direct evidence for the revolutionary active migration hypothesis. Additionally, factors such as intrapartum antibiotics exposure didn't significantly affect the diversity of the microbiota in the BM. Therefore, it is suggested that mothers continue to provide BM for their newborns during separation.